2014
DOI: 10.1158/1940-6207.capr-13-0424
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Cancer Risk and Mortality: A Systematic Review and Meta-analysis Taking into Account Biases and Confounders

Abstract: Previous meta-analyses have shown that the anti-diabetic agent metformin is associated with reduced cancer incidence and mortality. However, this effect has not been consistently demonstrated in animal models and recent epidemiological studies. We performed a meta-analysis with a focus on confounders and biases, including BMI, study type, and time related biases. We identified 71 articles published between January 1, 1966 to May 31, 2013 through Pubmed, ISI Web of Science (Science Citation Index Expanded), Emb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
263
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(290 citation statements)
references
References 104 publications
7
263
0
9
Order By: Relevance
“…In line with the mechanism exploration, the conclusion that metformin is related to the decreased CRC incidence among T2DM patients is also supported by our metaanalysis. Previous meta-analyses mostly supported reduced CRC risk associated with diabetes treated with metformin (Zhang et al 2011;Soranna et al 2012;Gandini et al 2014). The recent metaanalysis performed by Zhang et al (2011), including five studies, suggested a 37% reduction (95% CI: 0.50-0.79) of colon cancer incidence, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with the mechanism exploration, the conclusion that metformin is related to the decreased CRC incidence among T2DM patients is also supported by our metaanalysis. Previous meta-analyses mostly supported reduced CRC risk associated with diabetes treated with metformin (Zhang et al 2011;Soranna et al 2012;Gandini et al 2014). The recent metaanalysis performed by Zhang et al (2011), including five studies, suggested a 37% reduction (95% CI: 0.50-0.79) of colon cancer incidence, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Decensi et al (2010) included three articles in the meta-analysis of colon cancer incidence (Currie et al 2009;Libby et al 2009), which were all included in our study and in addition we also included eight more studies. Metaanalysis for all cancer risk by Gandini et al (2014) also found an Figure 3. Forest plot of colorectal cancer risk estimates for the relationship between use of metformin and CRC incidence among type 2 diabetic mellitus in different regions, study designs, and other anti-diabetes treatments.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…20 Metformin was shown to reduce cancer risk of 31% and cancer mortality of 34% in a recent meta-analysis. 21 In an another recent meta-analysis which included 265 studies, metformin or glitazones were linked with lower incidence of cancer but; oral antidiabetic medications called sulfonylureas, insulin and alpha-glucosidase inhibitors were linked with increased incidence of cancer (RR= 0.86, 0.93 vs 1.20, 1.21, 1.10 respectively). 22 Metformin was approved in Europe in 1958 and in USA in 1995 for use in type 2 diabetes mellitus which is an insulin sensitizer and mainly acts through inhibiting hepatic gluconeogenesis by activating LKB1 (liver kinase B1)/AMP-activated protein kinase (AMPK).…”
Section: Metformin and Cancermentioning
confidence: 99%